Pengedaran Farmasi Ilegal Golongan Kosmetika Dalam Perspektif Hukum Perlindungan Konsumen; Studi Putusan Pengadilan Negeri Martapura No. 361/pid.sus/2017/pn.mtp - Inayatul Mukaromah; Mustolih Sidradj (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThe problem of this research is the presence of business actors who sell pharmaceuticals in the form of cosmetics which are unfit for circulation for almost two years. But in its consideration, the Panel of Judges disagreed with the actions taken by BPOM in practice that were deemed not in accordance with the duties and functions as they should, so the Judge considered that this matter was detrimental to the defendant. This research method uses qualitative research by using a normative-empirical research approach. The study also uses a law in books approach and an empirical approach. The results showed that in the perspective of the UUPK, the defendant violated Article 4, 7 and 8 of Law Number 8 of 1999 concerning Consumer Protection. BPOM's actions towards the defendant in the Martapura District Court's decision No. 361 / Pid.Sus / 2017 / PN.Mtp are in accordance with the main duties and functions stipulated in Article 4 of Presidential Regulation Number 80 Year 2017 concerning BPOM RI.Keywords: Distribution, Pharmacy, Illegal Cosmetics, Consumer Protection, Legal Certainty, BPOM RI